"Do You Speak My Neighbourhood?" Language, Technology, and Proximity. Issue 2 (4th March 2017) - Westenberg, Peter; Rutten, Kris
ABSTRACT: The increasing emphasis on participation in both contemporary art and media practices implies that ethnography becomes an important framework to explore changing notions of place and interaction. This article analyses notions of participation, publicness, and proximity in the participatory artistic research projects Parlez-vous Saint-Gillois? and De Schaarbeekse Taal . It is explored how these projects deploy technology and language as means to create proximity, and what the issues are in creating art projects within a complex urban context. The notion of "co-presence" is introduced as a concept that moves beyond mere co-location in ethnographic research and participatory art practices. The argument is that the concept of co-presence opens new perspectives for artists and researchers to develop practices that examine space and locality, community and communication, proximity and interaction. At the same time, co-presence also raises issues about what can be considered as "public" or "public space" and what proximity entails, specifically in relation to media and technology. This article explores these issues by confronting theoretical perspectives with concrete examples from participatory artistic research projects.